PENGARUH FASILITAS KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR DINAS PENDIDIKAN MINAHASA TENGGARA - Thomas, Yeltsin Aprioke; Rorong, Arie Junus; Tampongangoy, Deysi (Sam Ratulangi University, 2017)
Abstract : The research is to know whether Facility (Computer, Office Working, Transportation, Electricity)influence to civil servant performance (work process, working condition, time in work, number of mistakes,amount in job type, job quality, punctuality, ability Work, evaluating ability.) At the Education Office ofSoutheast Minahasa District Under guidance. Where the data has been collected to 22 orga pimpinaan tosubordinate results o, 837 expressed relationships influence very strongly. Utuk determine the amount ofthe contribution (coefficient determinant coefficient determinant) Effect of work facility, on theperformance of civil servants in the office of Education Department National Minahasa Southeast result of70% and the remaining 30% is determined by other variables not examined by the author. To know theresult t arithmetic result is 6,432. So that obtained t table = 1.725. It turns out t count>> from t table or6.432> 1.725. Conclusion: correlation of variable X with Y or relationship Influence of work facility, toperformance of civil servant in South Minahasa Regency education office significant To find out the resultof simple regression equation about Influence of work facility, to performance of civil servant in office ofEducation Office of Regency of South Minahasa result significant The result is Y = Î± + bX = 33,137 +2,620 (.X). X = 22.545 Y = Î£Y = 25.95Keywords, Working facilities, Employe Perfomances